The effects of NaCl, KCl and MgCl2 on the germination of Brassica rapa var. parachinensis seed - Ghanad, Mona; Nulit, Rosimah; Go, Rusea; Yong, Christina Seok Yien (Science Publishing Corporation, 2016)
This study was conducted to determine seed germination on the mechanisms of salinity stress in B. rapa var. parachinensis (Hong kong choy sum). The type of experiment was a completely randomized design with three salinity treatment NaCl, MgCl2, and KCl and minimum four replications was used. Salinity treatment consisted of 0 (control), 50, 100, 150, 200, mM concentrations. The experiment was carried out under 70% relative humidity at 23°C with a photoperiod of 8:16 h light/dark. The germinated seeds were counted every day and germination percentage, seed vigor, seed tolerance, length of seedling and biomass seedling was measured. The data were analyzed by one-way ANOVA multiple comparison test followed by Duncan’s multiple range test.